EVALUATING ONE-LOOP LIGHT-CONE INTEGRALS BY COVARIANTIZING THE GAUGE-DEPENDENT POLE - Suzuki, A. T. (World Scientific Publ Co Pte Ltd, 1993)
Making sure that causality be preserved by means of ''covariantizing'' the gauge-dependent singularity in the propagator of the vector potential A(mu)(x), we show that the evaluation of some basic one-loop light-cone integrals reproduce those results obtained through the Mandelstam-Leibbrandt prescription. Moreover, such a covariantization has the advantage of leading to simpler integrals to be performed in the cone variables (the bonus), although, of course, it introduces an additional alpha-parameter integral to be performed (the price to pay).